Central nervous system manifestations of monogenic autoinflammatory disorders and the neurotropic features of SARS-CoV-2: Drawing the parallels - Renson, Thomas; Hamiwka, Lorraine; Benseler, Susanne (Frontiers in Pediatrics, 2022)
Central nervous system (CNS) involvement in monogenic autoinflammatory disorders (AID) is increasingly recognized and can be life threatening. Therefore, a low threshold to consider CNS disease should be maintained in patients with systemic inflammation. Hyperinflammation is also a key feature of severe acute COVID-19 and post COVID-19 entities such as multisystem inflammatory syndrome in children. Like AID, COVID-19 patients can present with severe CNS involvement. The impact of COVID-19 on AID and CNS involvement in particular is still obscure, nevertheless dreaded. In the current review, we synthesize the spectrum of CNS manifestations in monogenic AID. We explore common pathophysiological and clinical features of AID and COVID-19. Moreover, we assess the impact of immune dysregulation associated with SARS-CoV-2 infections and post COVID-19 hyperinflammation in AID. The striking commonalities found between both disease entities warrant caution in the management of AID patients during the current pandemic.